Data dsmcFoam+ case setup for the Orion Crew Module - Teschner, Tom-Robin (Cranfield University, 2021)
This material provides the OpenFOAM case setup files for the Orion Crew Module (OCM) in support of the submitted manuscript "Aerodynamic performance investigation through different chemistry modelling approaches for space re-entry vehicles using the DSMC method", presented at the UKACM 2022 conference. The case setup files are for the dsmcFoam+ solver and provide the mesh as well as the full setup for the Orion Crew Module (OCM) in 2D using the QK chemical model. All reactions are implemented for a 5-species flow.
Keywords: DSMC'; 'OPENFOAM'; 'Re-entry'; 'Fluid Mechanics'; 'Space Science'